The B Corp handbook : how to use business as a force for good - Honeyman, Ryan (BK business book., 2014)
Join a Growing movement: Learn how you can join a fast-growing global movement to redefine success in business-led by well-known icons like Patagonia and Ben & Jerry's as well as disruptive upstarts like Warby Parker and Etsy-recently covered by the New York Times, the Economist, the Wall Street Journal, Entrepreneur, and Inc. Build a better business: Drawing on best practices from 100+ B Corps, this book shows that using business as a force for good can help distinguish your company in a crowded market, attract and retain the best employees, and increase customer trust, loyalty, and evangelism for your brand.